Trans Mamminasata Bus Service Coverage Area in Corridors 2 and 3, Indonesia, using Network Analysis - Vita Fajriani Ridwan; Haeril Abdi Hasanuddin; Sarif Sarif (Institute of Research and Community Outreach - Petra Christian University, 2023)
This study examines issues related to the Trans Mamminasata Bus/Teman Bus, Indonesia, particularly in Corridors 2 and 3. Using primary and secondary data obtained from a survey, this study explores the service coverage area for three facilities (housing facilities, government and educational infrastructures) along the Corridors 2 and 3 using network analysis in Quantum GIS (QGIS). Two variables, pedestrian distance (400 meters) and cyclist distance (2000 meters), were applied in this study. The results showed that Corridor 2 served 86 infrastructures for the pedestrian distance variable and 367 infrastructures for the cyclist distance variable, while Corridor 3 served 89 infrastructures for the pedestrian distance variable and 217 infrastructures for the cyclist distance variable. The study found that the total service coverage area along Corridors 2 and 3 is wider for cyclists than for pedestrians. Moreover, this study highlights the presence of urban sprawl in the regions served by both Corridors.